2013
DOI: 10.1161/circulationaha.113.001470
|View full text |Cite
|
Sign up to set email alerts
|

The Global Cardiovascular Risk Transition

Abstract: Background It is commonly assumed that globally CVD risk factors are associated with affluence and Westernization. We investigated the associations of body mass index (BMI), fasting plasma glucose (FPG), systolic blood pressure (SBP), and serum total cholesterol (TC) with national income, Western diet, and (for BMI) urbanization in 1980 and 2008. Methods and Results Country-level risk factor estimates for 199 countries between 1980 and 2008 were from a previous systematic analysis of population-based data. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(105 citation statements)
references
References 35 publications
2
91
1
11
Order By: Relevance
“…Dahle and colleagues showed that high-normal blood glucose levels were associated with decreased delayed associative memory, reduced accuracy of working memory processing among women, and slower working memory processing among men, demonstrating that in healthy and not very old adults, normal but elevated values of recognized vascular risk factors were negatively associated with performance in agesensitive cognitive tasks [67]. Blood glucose levels within the normal range are mostly influenced by diet [68], so preventive interventions using low-glycemic index diets may have a large impact on public health. Authors' disclosures available online (http://j-alz.…”
Section: Discussionmentioning
confidence: 99%
“…Dahle and colleagues showed that high-normal blood glucose levels were associated with decreased delayed associative memory, reduced accuracy of working memory processing among women, and slower working memory processing among men, demonstrating that in healthy and not very old adults, normal but elevated values of recognized vascular risk factors were negatively associated with performance in agesensitive cognitive tasks [67]. Blood glucose levels within the normal range are mostly influenced by diet [68], so preventive interventions using low-glycemic index diets may have a large impact on public health. Authors' disclosures available online (http://j-alz.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid globalization, urbanization, ageing of society, and an increase in chronic diseases pose new challenges to modern health care systems (9,10). CVD is preventable, but physical inactivity, nicotine abuse and bad nutrition practices (11) (lost of traditional diet habits in new-industrial cultures) are leading to an increase of prevalence in most countries (12).…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…Hypertension is a major risk factor for cardiovascular disease (CVD) [1] and is of increasing public health importance in low- and middle-income countries [2]. Worldwide, there are almost one billion people living with hypertension [3] while different estimates have been found in Sub-Saharan Africa (SSA) [4].…”
Section: Introductionmentioning
confidence: 99%